Impact of Formal Controls on Client Satisfaction and Profitability in Strategic Outsourcing Contracts. Issue 4 (2nd October 2018) - Langer, Nishtha; Mani, Deepa
Abstract: The reach and impact of outsourcing has grown rapidly to include a variety of strategic objectives. Significant issues of cooperation and coordination in strategic outsourcing necessitate investments in formal controls that specify and monitor execution of the outsourced task to mitigate unforeseen contingencies and improve predictability in the attainment of desirable goals. In this study, we investigate the nature of formal controls in strategic outsourcing contracts and their impact on client satisfaction and financial performance. Specifically, using rich field data on 390 strategic outsourcing contracts, we examine the differential impact of output controls, activity controls, and capability controls on client satisfaction and vendor profitability. We find that activity and capability controls are positively associated with client satisfaction and profitability; in contrast, output controls differentially impact satisfaction and profitability, reflecting potential tradeoffs between the two outcomes. Our results, in addition to contributing to the research in control theory, provide actionable insights for technology vendors into the appropriate strategy and tactics required to compete efficiently and effectively in strategic services markets.